The Hubungan Defisiensi Vitamin D dengan Risiko Infeksi Saluran Pernapasan Bawah pada Dewasa - Ashilah Mumtaz Hakim; Chicy Widya Morfi (CV. Jasa Sukses Abadi, 2026)
Lower respiratory tract infections (LRTIs) remain a major public health problem in adults and contribute substantially to global morbidity and mortality. The risk of LRTIs increases among older adults and individuals with comorbid conditions, making the identification of modifiable risk factors essential. Vitamin D status has gained increasing attention due to its role not only in calcium homeostasis and bone health but also in the regulation of innate and adaptive immune responses. This literature review aims to evaluate the association between vitamin D deficiency and the risk and severity of LRTIs in the adult population. The review includes evidence from meta-analyses, randomized controlled trials, and cohort studies published within the past five years. The findings consistently show that serum 25-hydroxyvitamin D levels below 20 ng/mL are associated with a higher risk of pneumonia, prolonged hospital length of stay, and increased mortality. These associations are supported by biological mechanisms such as reduced production of antimicrobial peptides including cathelicidin, heightened pro-inflammatory immune responses, impaired macrophage and natural killer cell function, and weakened respiratory mucosal defenses. Several interventional studies indicate that vitamin D supplementation provides protective effects in individuals with vitamin D deficiency, particularly by reducing the incidence and severity of LRTIs, whereas the benefits appear limited in individuals with sufficient vitamin D levels. Overall, the evidence suggests that vitamin D screening, targeted supplementation, and comprehensive preventive strategies may play an important role in reducing the burden of LRTIs among adults.